2015
DOI: 10.1080/13811118.2015.1025119
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Anhedonia, Suicidal Ideation, and Suicide Attempts in a Large Student Sample

Abstract: Depression is a significant risk factor for suicide. Evidence suggests that anhedonia may be a symptom of depression that is uniquely associated with suicidality. However, exactly how anhedonia is related to suicide is unclear. To provide more specific evidence regarding this association, we investigated relationships between anhedonia, suicidal ideation, and suicide attempts. A large combined undergraduate sample completed the novel Specific Loss of Interest and Pleasure Scale (SLIPS), the Center of Epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
58
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 27 publications
11
58
0
3
Order By: Relevance
“…A recent study by Winer and colleagues similarly found that anhedonia independently predicted suicidal ideation in an inpatient sample of adults even when controlling for cognitive and affective depressive symptoms (Winer et al, 2014); specifically, reductions in anhedonia symptoms were associated with fewer suicidal thoughts at discharge from the hospital setting, highlighting the potential role of anhedonia as a treatment target. Similar results were found in a sample of college students (Winer et al, 2016). However, additional controlled investigations exploring the relationship between suicide and anhedonia are needed, given that there is presently no rapid-acting treatment for either.…”
Section: Introductionsupporting
confidence: 88%
“…A recent study by Winer and colleagues similarly found that anhedonia independently predicted suicidal ideation in an inpatient sample of adults even when controlling for cognitive and affective depressive symptoms (Winer et al, 2014); specifically, reductions in anhedonia symptoms were associated with fewer suicidal thoughts at discharge from the hospital setting, highlighting the potential role of anhedonia as a treatment target. Similar results were found in a sample of college students (Winer et al, 2016). However, additional controlled investigations exploring the relationship between suicide and anhedonia are needed, given that there is presently no rapid-acting treatment for either.…”
Section: Introductionsupporting
confidence: 88%
“…The heightened relationship between anhedonia and depression (and, to a lesser extent, anxiety) was elevated in part because we were assessing recent changes in anhedonia, which have previously been found to be associated with other virulent depressive symptoms (Joiner et al, 2003; Winer et al, 2016b; Winer et al, 2014a; Winer et al, 2014b). Increase in anhedonia is thus distinguishable from trait physical anhedonia (Shankman et al, 2010), and is likely more associated with anticipatory than consummatory disturbance (Thomsen, 2015; Winer et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Participants ( N = 747) completed measures online as part of a larger study (Nadorff et al, 2014; Winer et al, 2016a; Winer et al, 2016c) in exchange for course credit. Participants who completed all questionnaires ( N =652) were included, and the sample consisted of 43% males and 57% females, ages 18–22 ( M = 18.9, SD = 1.43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals experiencing anhedonia can have difficulty motivating themselves to pursue rewarding stimuli, thus causing dysfunction. Recent changes in anhedonia—that is, the loss of interest or pleasure—may be especially associated with depression [68]. This is because a loss signals that a person previously enjoyed and/or had interest in certain activities or social settings (i.e., had a functioning reward system), but that he or she is now getting less reward from those experiences [9,10].…”
Section: Introductionmentioning
confidence: 99%